sierracicimorris sierracicimorris
  • 01-10-2020
  • Mathematics
contestada

Write an equivalent expression for (x - 11)(x + 9).

Respuesta :

cxrmela cxrmela
  • 01-10-2020

Answer:

x²-2x-99

Step-by-step explanation:

(x-11)(x+9) - foil method

x times x = x squared

x times 9 = 9x

-11 times x = -11x

-11 times 9 = -99

x squared + 9x + 11x + -99

x squared-2x-99

Answer Link

Otras preguntas

How is it possible for Mercury to have frozen ice ?
Which equation has the same y-intercept as y=4x-3?a. y-3=x              b. y=8x+3    c. 3-y=4x      d. y=-3+8xWhich of the following is the equation of the line
(10y^3+20y^2+55y)/5y
Historians of china have traditionally dated the beginning of Chinese civilization to the founding of the what??
Prove that (x^5)-(x^2)+2x +3=0 has at least one real root. Prove that x=cosx has at least one solution.
Scarcity is the condition of not having enough goods and services to satisfy everyone's?
Can someone use the word delta in a sentence
How were life forms affected by the rise in atmospheric oxygen levels that began 2.2 billion years ago?
Data are drawn from a symmetric and bell shaped distribution with a mean of 120 and a standard deviation of 5. There are 900 observations in the data set. What
How is it possible for Mercury to have frozen ice ?